Acute aortic regurgitation following fibrous strand rupture of aortic valve successfully diagnosed by transesophageal echocardiography. Issue 5 (30th March 2018) - Nishida, Hidefumi; Suenaga, Etsuro; Ishii, Katsuhisa
Abstract : Fibrous strand rupture is a rare cause of acute aortic regurgitation, but is a serious condition because of acute massive regurgitation. Therefore, prompt and accurate diagnosis is required. We saw a 53‐year‐old man who presented with acute dyspnea without evidence of infection. Transesophageal echocardiography revealed severe aortic regurgitation because of fibrous strand rupture. We performed surgery and found that the fibrous strand of the right coronary leaflet was ruptured. In cases of acute aortic regurgitation, the rupture of fibrous strand should be considered and transesophageal echocardiography would be very useful to diagnose it.